2002
DOI: 10.1093/jat/26.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Overdosage with Nefopam (Acupan®)

Abstract: This paper presents a fatality due to massive, intravenous self-administration of nefopam (Acupan), a non-opiate central analgesic, in a 37-year-old female. Nefopam was measured in various postmortem samples by means of high-pressure liquid chromatography coupled to mass spectrometry via an ionspray interface. Heart blood concentration was 4.38 microg/mL and exceeded by approximately 30 times the highest therapeutic levels with the usual reservations concerning possible postmortem redistribution. This is only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…There are some cases reported in literature of Nefopam fatal overdoses characterized by disorientation, aggressive convulsions, cardiac arrhythmia and respiratory depression [40]. Important cerebral edema was found postmortem in these patients [41].…”
Section: Adverse Effects and Contraindicationsmentioning
confidence: 91%
“…There are some cases reported in literature of Nefopam fatal overdoses characterized by disorientation, aggressive convulsions, cardiac arrhythmia and respiratory depression [40]. Important cerebral edema was found postmortem in these patients [41].…”
Section: Adverse Effects and Contraindicationsmentioning
confidence: 91%
“…8 Life-threatening effects have been reported in relation to nefopam overdose, however, including rare fatal overdoses characterized by convulsions and arrhythmia. 26,27 An accidental overdose was reported in a 77-year-old man who developed acute neurological impairment and renal failure. 28 Overdose was unlikely in the present study, however, since a low dose was used and all patients were closely observed in the ICU after surgery.…”
mentioning
confidence: 99%
“…In cases of generalized tonic-clonic seizure followed by fatality, the serum concentration of nefopam was in the range of 4.3 to 11.9 mg/L. [ 13 , 14 ] There has also been a case report of status epilepticus occurring in a patient who was treated with a continuous infusion of nefopam. [ 6 ] In this case, the patient was treated with various pain relievers because of back pain, and 80 mg of nefopam was mixed with 1 L of plasma solution and administered at an infusion rate of 42 mL/h.…”
Section: Discussionmentioning
confidence: 99%